A new species of Aponogeton (Aponogetonaceae) from India with critical notes on embryo morphology - Yadav, Shrirang Ramchandra (Phytotaxa, 2017)
Aponogeton wolfgangianus is described from Panamaram village in Wayanad district of Kerala, India. The morphology of the embryo, its significance in delimiting species and interspecific relationships have been discussed. Embryo morphology is species specific in Aponogeton and is of diagnostic value.